Creative Process Of Extracurricular Nasheed Al-Mutazam Integrated Boarding High School In Kuningan Barat Jawa Barat - Herlambang, Agam; Suharto, Suharto; Susetyo, Bagus (Universitas Negeri Semarang, 2020)
Nasyid extracurricular students at SMAIT Al-Multazam are students with a lack of musical experience but produce musical abilities to create nasyid works. The aim of this research is to find out and describe how the creative process of nasyid extracurricular students in creating nasyid works. This research use desciptive qualitative approach. Data collection techniques used were interviews, observation, and study of documents. The results of this study the creative process carried out by nasyid extracurricular students includes 4 stages, namely determining ideas, the process of creating nasyid lyrics, determining the chords in nasyid song lyrics, the method of composing chords on nasyid songs and the creation of a nasyid work. The conclusion is that the Nasyid extracurricular students are still in the learning stage but choose to pursue it to create a nasyid work so that it has a creative process to create nasyid works that can produce a work.